Devotion to Clinical Psychology. To the anniversary of Irina Fedorovna Roshchina - N.V. Zvereva (Клиническая и специальная психология)
The work is dedicated to the anniversary of the renowned Russian neuropsychologist, I.F. Roshchina, who celebrated her anniversary in January 2024. The article highlights the main milestones in her biography and identifies her main areas of scientific interest, including: the study of normal and pathological aging, the methodology and diagnostic tools of clinical psychology, the theoretical and methodological issues of medical (clinical) psychology, as well as issues related to the training and education of young professionals and the preservation of the traditions of the Moscow School of Clinical Psychology. A brief review of her recent publications reflects I.F. Roshchina's long-standing work as a researcher, teacher, and practitioner. The staff of the Department of Neuro- and Patho-psychology of Development at MSUPE cordially congratulates Irina Fedorovna on her anniversary, wishing her good health, worthy students, and success in the development of neuro-herontology and clinical psychology.